Relationship of Haemoglobin and C Reactive Protein level with Different Types of Heart Failure Patients - Morshed, Mahboob; Islam, Md Joynul; Haseen, Fariha; Haque, Mohammad Ahtashamul; Amin, ABM Ruhul (Journal of Current and Advance Medical Research, 2019)
Background: Initial level of haemoglobin and CRP level is important issue among the different type of heart failure patients for their in-hospital outcomes. Objective: The purpose of the present study was to see the relationship of haemoglobin (Hb) and CRP level with different types of heart failure patients. Methodology: This cross-sectional study was conducted in the Department of Cardiology at Mymensingh Medical College, Mymensingh, Bangladesh from December 2010 to November 2011 for a period of two (2) years. Patients of ACS who were presented within 12 hours of chest pain were included as study population. Study population were categorized in four groups according to the level of hemoglobin and C-reactive protein. Blood sample was collected for baseline laboratory investigations like Troponin-I, random blood sugar (RBS), blood urea, serum creatinine, lipid profile, Hemoglobin and CRP level. Sample were then send to standard laboratory/Biochemistry department of MMCH. Result: The mean age of the population was 52.18±8.88 years. Statistically non-significant mean age difference among the groups. Significant difference of mean left ventricular (LV) ejection fraction was found among the groups (p=0.005). Maximum patient in group 1 (48.5%) had ejection fraction in the range of 40 to 50%, compare to group 2(32.0%), group 3 (11.1%) and group 4 (5.8%). The heart failure was statistically significant in Killip class I (p=0.000) and Killip class II (p=0.000). Conclusion: In conclusion haemoglobin and CRP level of acute coronary syndrome patients is statistically significantly associated with different types of heart failure Journal of Current and Advance Medical Research 2019;6(2):101-105